Correlation between serum circRNA and thyroid micropapillary carcinoma with cervical lymph node metastasis. Issue 47 (20th November 2020) - Yang, Wenwen; Bai, Chao; Zhang, Li; Li, Zongbao; Tian, Ye; Yang, Zhenwei; Wang, Liang; Wu, Wennian
Abstract : Abstract: The study aims to characterize the circular RNA (circRNA) expression profile that is functionally related with the invasiveness of papillary thyroid microcarcinoma (PTMC). A total of 13 pairs of female patients with non-invasive PTMC or lymph node metastasis PTMC (PTMC (L)) were included and the serum RNA was obtained. CircRNA microarray was performed to identify the circRNA expression profile. Real time-PCR was used to verify circRNA expression. Bioinformatic approaches were adopted to annotate the function of differentially expressed circRNAs and construct the circRNA-miRNA-mRNA network. In total, 400 significantly upregulated and 290 significantly downregulated circRNAs were identified in PTMC (L) compared with PTMC. Among them, 10 circRNAs were selected and validated by real time-PCR. Putative microRNAs (miRNAs) that could bind to the differentially expressed circRNAs were predicted. Gene Ontology and Kyoto Encyclopedia of Genes and Genomes analyses of target genes of the differentially expressed circRNAs revealed that these circRNAs may play an important role in lymph node metastasis. Finally, circRNA targeted miRNAs were predicted and a circRNA-miRNA-mRNA network was constructed for hsa_circRNA_404686. Our results showed that several circRNAs, such as hsa_circRNA_404686, may serve as promising diagnostic marker for PTMC (L) in female.